2001
DOI: 10.1590/s0001-37652001000200008
|View full text |Cite
|
Sign up to set email alerts
|

Watery and dark axons in Wallerian degeneration of the opossum's optic nerve: different patterns of cytoskeletal breakdown?

Abstract: In this paper we report a qualitative morphological analysis of Wallerian degeneration in a marsupial. Right optic nerves of opossums Didelphis marsupialis were crushed with a fine forceps and after 24, 48, 72, 96 and 168 hours the animals were anaesthetized and perfused with fixative. The optic nerves were immersed in fixative and processed for routine transmission electron microscopy. Among the early alterations typical of axonal degeneration, we observed nerve fibers with focal degeneration of the axoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 47 publications
8
30
0
Order By: Relevance
“…Similar to the study using optic nerve crush injury, the current study also identified watery and dark degeneration in the axons [66]. Both patterns were observed at 72 hrs and 7 days of injury.…”
Section: Discussionsupporting
confidence: 85%
“…Similar to the study using optic nerve crush injury, the current study also identified watery and dark degeneration in the axons [66]. Both patterns were observed at 72 hrs and 7 days of injury.…”
Section: Discussionsupporting
confidence: 85%
“…The axoplasm degeneration we observed follows the same pattern as that described for vertebrates [Narciso et al, 2001]. It starts by breakdown of microtubules and other axonal organelles.…”
Section: Discussionsupporting
confidence: 82%
“…This indicates an asynchronous pattern of degeneration of nerve fi bers in arthropods, similar to what is observed in vertebrate optic nerve fi bers [Narciso et al, 2001;Marques et al, 2003]. The reason why a certain fi ber starts to degenerate regardless of what is happening to the adjacent similar fi ber is unknown.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This event is called granular disintegration of the axonal cytoskeleton resulting in complete degradation of axonal organelles and proteins and is the main ultra-structural characteristic of axons undergoing WD in the PNS. In central nerve fibers, axon disruption may present in two distinct patterns of axoplasm degeneration, as based on the ultra-structural aspect of the axoplasm (Figure 1) (Narciso et al, 2001). Fig.…”
Section: Overview Of Wallerian Degenerationmentioning
confidence: 99%